2016
DOI: 10.4236/ojs.2016.66085
|View full text |Cite
|
Sign up to set email alerts
|

The Efficiency Measurement of Indonesian Universities Based on a Fuzzy Data Envelopment Analysis

Abstract: The main objective of this study is to measure the relative efficiency of Indonesian universities in 2015. There are twenty five DMUs with four inputs and five outputs that are analyzed. Due to the low number of Indonesian scientific publications, this study analyses the performance of the top 25 universities based on the Webometrics ranking as it has been used as one of the indicators of university achievements by the Higher Education of Indonesia. The Data Envelopment Analysis (DEA) is used to obtain the sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…CRS is one of the most common procedures for comparisons of the performance of multiple large firms. Fuzzy DEA can be more appropriate in most other circumstances [14]. Numerous researchers have investigated the presence of both qualitative and quantitative factors [15].…”
Section: Methodsmentioning
confidence: 99%
“…CRS is one of the most common procedures for comparisons of the performance of multiple large firms. Fuzzy DEA can be more appropriate in most other circumstances [14]. Numerous researchers have investigated the presence of both qualitative and quantitative factors [15].…”
Section: Methodsmentioning
confidence: 99%
“…In the context of developing countries, such as Indonesia, efficiency is still a big problem for public higher education. Some leading universities have problems in managing resources to produce world class university outputs (Mahmudah & Lola, 2016). The same thing also happens in eight teacher training universities as they struggle to produce their educational output (Jati, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This study employed two DEA models and the result showed that 12 and 17 provinces out of 34 provinces in Indonesia are efficient and three environmental variables significantly affect the efficiency score. Another study examined efficiency at the university level (Mahmudah & Lola, 2016). This study examined the top 25 universities in Indonesia in 2015 using DEA and fuzzy DEA.…”
Section: Introductionmentioning
confidence: 99%